Soils and vegetation of the permafrost floodplain of the small river Tenyakha (Messoyakha basin, Western Siberia) - Sergey V. Loiko; Ivan V. Kriсkov; Nikita V. Shefer; Irina Nedyak; Rinat M. Manasypov; Sergey P. Kulizhskiy (Acta Biologica Sibirica)
The soils and vegetation of Arctic floodplains are vulnerable to global warming because, in addition to climate change, they are affected by the changing hydrological regime of rivers. However, for river floodplains in large Arctic regions, such as the Yamalo-Gydan ecoregion, even descriptive field studies are still very incomplete. Therefore we studied the vegetation and soils of the floodplain of the small Tenyakha River in the south of the Gydan Peninsula. Two types of floodplain are described. The first type is represented by a floodplain on channel slopes. The second is a meander with ridges and depressions in between. Plant communities of the first type of floodplain have a higher diversity of higher plants than communities of the second type. Plant communities of microtopographic depressions and concave slopes have a lower diversity of vascular plants. The soil-forming deposits are predominantly sandy. According to the WRB, almost all the soils studied are classified as Fluvisols, except for one, classified as Arenosol, which is present in modern aeolian deposits on the floodplain ridge. All soils within two meters of the surface contain permafrost. There are soils with a humus horizon more than 20 cm thick (Gleyic Orthofluvic Fluvisol (Epiarenic, Endosiltic, Ochric)). The Munsell value of these soils is the same as that of the humus horizons of the zonal soils of the southern taiga and subtaiga. We have not detected a distinct effect of climate change on the soils. Further research is needed to confirm this.